2008
DOI: 10.1111/j.1365-2567.2008.02807.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulin G‐mediated regulation of the murine immune response to transfused red blood cells occurs in the absence of active immune suppression: implications for the mechanism of action of anti‐D in the prevention of haemolytic disease of the fetus and newborn?

Abstract: SummaryAnti-D has been widely and effectively used in Rhesus blood group D negative mothers for the prevention of haemolytic disease of the fetus and newborn; its mechanism of action however, often referred to as antibody-mediated immune suppression (AMIS), remains largely unresolved. We investigated, in a murine model, whether active immune suppression or clonal deletion mediated by anti-red blood cell (RBC) immunoglobulin G (IgG) could explain the phenomenon of AMIS. Transfusion of IgG-opsonized foreign RBCs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…Tetanus toxoid and diphtheria toxoid used for the enzyme‐linked immunosorbent assays (ELISAs) were purchased from Listlabs‐Cedarlane (Hornby, Ontario, Canada). IgG anti‐SRBC and IgG anti‐NP were prepared and purified from sera from BALB/c mice hyperimmunized against SRBC‐ or NP 30 ‐keyhole limpet hemocyanin (Biosearch Technologies) and IgG purified using protein G‐agarose column chromatography (Pierce, Rockford, IL) as detailed elsewhere 28 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tetanus toxoid and diphtheria toxoid used for the enzyme‐linked immunosorbent assays (ELISAs) were purchased from Listlabs‐Cedarlane (Hornby, Ontario, Canada). IgG anti‐SRBC and IgG anti‐NP were prepared and purified from sera from BALB/c mice hyperimmunized against SRBC‐ or NP 30 ‐keyhole limpet hemocyanin (Biosearch Technologies) and IgG purified using protein G‐agarose column chromatography (Pierce, Rockford, IL) as detailed elsewhere 28 …”
Section: Methodsmentioning
confidence: 99%
“…There is evidence that the AMIS effect may be restricted to B cells, because T‐cell responses can occur under AMIS conditions 18,20,24‐28 . Furthermore, AMIS may not be related to tolerogenic mechanisms because a subsequent antigen challenge after complete AMIS induction resulted in an antibody response 29,30 …”
mentioning
confidence: 99%
“…Although the transfusion of xenogenic SRBC has been widely used to study IgG-mediated immune suppression mechanisms by us (12,13,(18)(19)(20)(21) and others (16,(22)(23)(24)(25), validation against an allogenic mouse model is essential as SRBC do not meaningfully enter the mouse circulation and also contain inflammatory ligands and the actual Ags on the SRBC have not been definitively established (3,26). Contrary to the transfusion of allogeneic mouse RBC that circulate with a normal life span (27,28), SRBC are cleared from circulation within a few hours (29,30).…”
mentioning
confidence: 99%
“…Because the APC function of B cells depends on successful priming (24,25), B cell priming is probably either absent, down-regulated, or otherwise changed under AMIS conditions. We and others have observed that immunization at early time points after AMIS induction did not lead to suppression, but rather generated a secondary-like Ab response (19,33,34). This secondary-like response, a priori, excludes B cell anergy, B cell clonal deletion, or B cell clonal silencing as likely mechanisms for the observed lack of Ag-specific B cell APC function in vitro.…”
Section: Discussionmentioning
confidence: 99%